STRATEGI KOMUNIKASI PERSUASIF OVO DALAM PANDEMI COVID-19 MELALUI INSTAGRAM @OVO_ID - Rambe, Ira Hasianna (Universitas Tribhuwana Tungga Dewi, 2022)
The internet technology currently in demand is Instagram. This technology is able to provide and as a medium of information as fast as lightning with a blend of video, audio and visual. So it attracts the audience to use Instagram. In the current condition of the COVID-19 pandemic, Instagram is able to be a place for sharing information and being a marketing medium. As done by OVO. Companies in the field of fintech, which are incessantly using social media Instagram as a product marketing media. OVO first posted the